2021
DOI: 10.1017/s0033291721002749
|View full text |Cite
|
Sign up to set email alerts
|

The relative and interactive impact of multiple risk factors in schizophrenia spectrum disorders: a combined register-based and clinical twin study

Abstract: Background Research has yielded evidence for genetic and environmental factors influencing the risk of schizophrenia. Numerous environmental factors have been identified; however, the individual effects are small. The additive and interactive effects of multiple risk factors are not well elucidated. Twin pairs discordant for schizophrenia offer a unique opportunity to identify factors that differ between patients and unaffected co-twins, who are perfectly matched for age, sex and genetic background. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 68 publications
1
21
0
Order By: Relevance
“… 26 No statistically significant evidence was found in a subpopulation of first-episode psychosis cases in the same sample 47 as all the CIs included zero. The 2 other studies 48 , 59 did not find evidence of an additive interaction but it is likely the studies were underpowered. It is possible that other studies ran interaction analyses but did not report negative results, resulting in publication bias.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“… 26 No statistically significant evidence was found in a subpopulation of first-episode psychosis cases in the same sample 47 as all the CIs included zero. The 2 other studies 48 , 59 did not find evidence of an additive interaction but it is likely the studies were underpowered. It is possible that other studies ran interaction analyses but did not report negative results, resulting in publication bias.…”
Section: Discussionmentioning
confidence: 92%
“… 48 Lastly, a Danish twin study in 56 schizophrenia spectrum proband pairs, 49 healthy control pairs, and 6 individual probands found no evidence of an interaction between schizophrenia PRS and childhood adversity (OR = 1.00, 95% CI = 0.48, 2.07, P = .999). 59 …”
Section: Resultsmentioning
confidence: 99%
“…Consistent with imaging data, molecular markers are also indicative of accelerated cortical aging in schizophrenia [10], possibly contributing to a markedly increased rate of dementia in late life for people with schizophrenia [11]. Accordingly, deciphering the mechanisms through which chronic stress [12,13], neuroinflammation [14][15][16][17][18], redox dysregulation [19,20], drug abuse [21][22][23] and antipsychotic treatment [24,25] could accelerate cortical tissue loss during late neurodevelopment becomes critical [8,9]. Iron, the most abundant transition metal in the brain, has been implicated in these potential insults [26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 73%
“…Prospective epidemiological studies have consistently reported an association between cannabis use and an increased risk for subsequent psychotic experiences and psychotic disorders 1 3 . However, only a minority of individuals who use cannabis will eventually develop a psychotic disorder.…”
Section: Introductionmentioning
confidence: 99%